LINGUISTIC PORTRAITING OF THE COVID-19 PANDEMIA IN THE PRESS OF RUSSIA AND GERMANY - S. Serebriakova; A. Milostivaya (Гуманитарные и юридические исследования)
The article studies verbal means describing the COVID-19 pandemic in Russian and German print press. The topicality of the study is associated with critical discourse analysis of the media content within the framework of the spread of coronavirus infection in the irst half of 2020. At the same time, attention is focused not only on the formal linguistic features of the newspaper text, but also on extralinguistic factors of its production, which made it possible to study the wide communicative background of the text. It appears to be especially important for studies of socially signiicant events affecting both individual countries and the global world as a whole. The scientiic novelty is determined by the fact that the article for the irst time speciies communicative-pragmatic potential of speech methods used in portraying a pandemic in the press of Russia and Germany. The authors proceed from the assumption that in addition to the content-factual information in the press every time axio-logical assessment of the reported information is actualized. Therefore, in the process of persuasiveness study in news- paper discourse, it is relevant to consider communicative strategies for presenting depicted denotative content. The main research method in this article is discourse analysis based on the principle of functionalism. At the same time, the research was focused on the interpretation of linguistic manipulation devices in press coverage of the two countries in the period of the coronavirus pandemic: introduction of factual information into a negatively assessed context, personalization in presentation of negative consequences of the described phenomenon, portrayal of evidence as guilt, correlation of unmotivated similarities with negatively assessed entity, choice of measure units as a tool of linguistic manipulation, imposing of presupposition that does not require critical discussion, use of metaphors for persuasive purposes, link to an unknown source of information.